Does commercial debarking of a medicinal tree impact its population-spatial structure? The case of Hintonia latiflora in Mexico - Vásquez-Cortez, Vicente Florencio; Beltrán-Rodríguez, Leonardo; Ángeles-Pérez, Gregorio; Romero-Manzanares, Angélica; Garcia-Moya, Edmundo; Luna-Cavazos, Mario; Caballero, Javier; Blancas, José; Martínez-Ballesté, Andrea; Montoya-Reyes, Francisco (Instituto de Ecología, A.C., 2020)
The population structure and the patterns of spatial distribution and correlation among developmental stages of Hintonia latiflora, a species threatened in Mexico by the commercial harvest of its bark, are documented. Six plots (three in harvested sites and three in not harvested ones) of 20 m × 100 m were established for the census of all plants and they were categorized into three stages of development based on the total height and basal diameter; all individuals were located by their cartesian coordinates. The population structure was analyzed by a density histogram; whereas bias and kurtosis were used to determine the harvest effect on size categories. Univariate and bivariate spatial patterns were determined using Ripley's L(t) and L12(t) functions, respectively, and the statistical significance was 99% using Monte Carlo simulations. Density between harvested sites vs. not harvested was statistically different (p < 0.013), but the population structure was similar, with a positive asymmetric distribution pattern (S3 = 0.947 and S3 = 1.063) and leptokurtic (S4 = 2.006 and S4 = 2.400). The univariate distribution pattern in all cases was aggregated (L(t) > 0), whereas the spatial correlation in populations subject to debarking reflected a combination between independence and spatial attraction at different distances. This information provides a basis for the sustainable management of H. latiflora and represents the first study in Mexico that analyzes the debarking of a medicinal resource on its population-spatial structure.